2020
DOI: 10.2298/sos2003269j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperatures and foaming agent content to the physical and structural properties of wollastonite based foam glass-ceramics

Abstract: This study aims to fabricate low-cost foam glass-ceramic using soda-lime-silica (SLS) glass waste and clamshells (CS) as foaming agent in content between 1 and 12 wt.% by conventional powder processing method. The samples were undergoing sintering process between 700 and 1000?C with holding time of 30 minutes and characterized according to the physical and structural properties. Samples containing 3 wt.% CS treated at 800?C show the greatest size of porosity. As the sintering temperature incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…When varying the sintering temperatures (T sint ), no clear linear dependency with distortions was found, which contradicted what D. Yang et al [35] concluded using borosilicate glass and temperatures between 640 • C and 680 • C. However, when compared with research results using recycled soda-lime-silica glass from windshields, as presented in Gualberto et al [36], or with recycled sauce bottles in Jaafar et al [40], similarities could be found. Namely, the specimens sintered at 800 • C had the smallest shrinkage.…”
Section: Preliminary Study Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…When varying the sintering temperatures (T sint ), no clear linear dependency with distortions was found, which contradicted what D. Yang et al [35] concluded using borosilicate glass and temperatures between 640 • C and 680 • C. However, when compared with research results using recycled soda-lime-silica glass from windshields, as presented in Gualberto et al [36], or with recycled sauce bottles in Jaafar et al [40], similarities could be found. Namely, the specimens sintered at 800 • C had the smallest shrinkage.…”
Section: Preliminary Study Resultsmentioning
confidence: 72%
“…Gualberto et al found that increasing the sintering temperature up to 800 • C would lower the density of the specimens since the crystallization would occur before the sintering was complete, causing a rapid increase in viscosity and successively less dense materials [36]. Jaafar et al [40] state that a further increase in the sintering temperature to values above 800 • C, together with secondary effects, would lower the viscosity of the glass and provoke the increase in density, which can result in greater shrinkage. However, these comparisons are limited in the sense that the materials used, processing techniques, and sintering conditions are different from the ones used in this study.…”
Section: Preliminary Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work done by Anuar et al has highlighted the effect of sintering temperature on the structural and optical properties of ZnO-CHA [21]. The solid-state sintering process has considerably provided an alternative route not only due to its cost efficiency and simplicity in preparing the precursors, but also offers a significant improvement in physical, mechanical, and optical properties by merely adjusting the sintering environment [22]. Though sintering time does not play an essential role as sintering temperature, yet it can provide significant clarification through the studied properties.…”
Section: Introductionmentioning
confidence: 99%
“…Soda lime silica (SLS) glass is an abundant waste material due the cost effective for producing highly density sintered ceramics. SLS glass contains majority of 70 wt% of silicon dioxide (SiO 2 ) and minority of other compounds such as 13 wt% of sodium oxide (Na 2 O) and 11 wt% of calcium oxide (CaO) [10][11]. The addition of this source of silica in metal oxide varistor (MOV) is able to improve nonlinear coefficient of the varistor, electrical and thermal stability [12].…”
Section: Introductionmentioning
confidence: 99%